2014
DOI: 10.1007/s10661-014-3927-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving artificial forest biomass estimates using afforestation age information from time series Landsat stacks

Abstract: China maintains the largest artificial forest area in the world. Studying the dynamic variation of forest biomass and carbon stock is important to the sustainable use of forest resources and understanding of the artificial forest carbon budget in China. In this study, we investigated the potential of Landsat time series stacks for aboveground biomass (AGB) estimation in Yulin District, a key region of the Three-North Shelter region of China. Firstly, the afforestation age was successfully retrieved from the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…The stratification of forest types based on tree species and environmental variables can provide the potential of improving the estimation of forest AGB [22,32,33]. Moreover, incorporating the tree age into the estimation models can also lead to an improvement of the AGB/carbon sequestration estimates and can reduce the overestimation and underestimation [64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stratification of forest types based on tree species and environmental variables can provide the potential of improving the estimation of forest AGB [22,32,33]. Moreover, incorporating the tree age into the estimation models can also lead to an improvement of the AGB/carbon sequestration estimates and can reduce the overestimation and underestimation [64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…Lefsky et al [66] mapped the forest stand age using the time series of Landsat images, then estimated the AGB of young stands using Lidar data in western Oregon, USA, and found that the estimation models were appropriate for the forests with the classes of ages 14.5 to 20.5 years but resulted in overestimations for the smaller age classes. Based on the years in which the trees were planted, Liu et al [67] also obtained and added the age variable into their linear regression models to estimate the AGB of plantations using Landsat images. The studies indicate that taking tree ages into account would obtain a considerable improvement in estimating AGB.…”
Section: Introductionmentioning
confidence: 99%
“…China is the country possessing the largest artificial forest in the world [1]. Considering the timber production and environmental adaptability, plantations in North China mainly rely on poplars.…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions, we build on decades of studies using time series of vegetation indices derived from satellite imagery to model primary productivity (Tucker 1979, Paruelo et al 1997, tree growth (Wang et al 2004), and plantation wood production (le Maire et al 2011, Liu et al 2014, Dube et al 2015. We also use time series of satellite observations to map plantations on the landscape (Dong et al 2013, Qiao et al 2016 and to identify harvest and subsequent forest regrowth (DeVries et al 2015).…”
Section: Introductionmentioning
confidence: 99%